Fabrication of melamine trimetaphosphate 2D supermolecule and its superior performance on flame retardancy, mechanical and dielectric properties of epoxy resin. (15th November 2021) - Qin, Peifan; Yi, Deqi; Hao, Jianwei; Ye, Xinming; Gao, Ming; Song, Tinglu
Abstract: To improve the flame retardancy, mechanical and dielectric properties of epoxy resin (EP), a novel two-dimensional (2D) supermolecule, melamine trimetaphosphate (MAP), is successfully synthesized using melamine (MA) and sodium trimetaphosphate (STMP) in aqueous solution. Its chemical, crystalline structure and thermal stability are thoroughly characterized by Fourier transform infrared (FTIR), nuclear magnetic resonance (NMR), X-ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscope (TEM), atom force microscope (AFM) and thermo-gravimetric analysis (TGA) techniques. Then EP-MAP composites are prepared, and their morphologies are assessed by SEM, thermal stability by TGA, fire retardancy by limiting oxygen index test (LOI), vertical burning standard test (UL-94), and cone calorimeter tests, mechanical properties by stress strain tests, and dielectric properties by impedance analyzer. The results show that the MAP layers are formed by a 3:1 combination of MA and STMP rings via intermolecular hydrogen bonding. The MAP sheets with a thickness of around 2 nm show high thermal stability. Compared to pure EP, the thermal stability of EP-MAP is improved, and EP-MAP composite can achieve 30.0% of LOI value and UL-94 V-0 rating with only 4% MAP. Meanwhile its peak of heat release rate is reduced by 65.6% and the smoke release is highly suppressed in the cone calorimeter test. The typical intumescent flame retardancy effect and phosphorus-nitrogen ( P –N) effect during the combustion of EP-MAP are demonstrated by X-ray photoelectron spectroscopy (XPS) and thermogravimetric analyzer coupled with Fourier transform infrared analysis of evolving products (TGA-FTIR). Due to the uniform dispersion of MAP in EP matrix, the mechanical and dielectric properties of EP-MAP are also significantly enhanced. Graphical abstract: Image 1